A combined boundary element and an analytical approach to grounding mesh modeling in a multi-layer soil - Mujezinovic, Adnan; Mulaosmanovic, Ajdin; Muharemovic, Alija; Turkovic, Irfan; Bajramovic, Zijad (Elektrotehniski Vestnik, 2017)
This paper deals with a combined computer-aided numerical - analytical approach to calculation of the grounding. The electromagnetic theory on which the presented mathematical model is based is described. The model which is based on boundary element method, Aitken's δ^sup 2^ algorithm and grounding potential non-uniformity correction factors is explained in detail. A special attention is paid to the selection of an appropriate Green's function in the calculation of parameters of a large and complex grounding mesh for a homogeneous and a two-layer soil. Finally, the model is used to calculate the grounding mesh parameters of a real power substation with complex geometry.